IN-SIGHTSEEING HERITAGE VS TOURISTING - Folgado, Madalena (European Scientific Journal, ESJ, 2015)
Instead of a destination, this article aims to draw an approach path to meaning. In this sense, we will build up our answer through five senses, with the intention of emphasizing architectural experience formative effect; paradoxically, focusing on re-placing what could be ephemeral for something more permanent and powerful for our everyday lives. The chosen place is Santa Bárbara Inn, at Oliveira do Hospital, designed by Manuel Tainha, about to be reopened after being renovated under contemporary hospitality requirements. Time will be challenged through landscape contemplation; as a result, we will share several instants – in-sights of embodied affection. We believe that, in opposite to the flash shots from tourists cameras, capturing the instant during the architectural experience – in-sightseeing – allows us to expand consciousness and re-create new bonds; from this particular place to other places. By fulfilling our baggage with a strengthened consciousness, hopefully, we decrease heritage burden, after all, all we need is to develop simple and sustainable strategies to move forward.